AN INVESTIGATION OF EMPHATIC LISTENING IN ENGLISH MEETING AT BENTENG PANYNYUA ENGLISH CLUB MAKASSAR (BPEC) MAKASSAR - Anggraeni N, Ardilah; Ariana; Hafid, Hilda (FKIP Unismuh Makassar, 2024)
The purpose of this study was to find out whether there was Emphatic Listening and how it was implemented at Benteng Panynyua English Club (BPEC) Makassar. This study uses a qualitative descriptive design. The research subjects in this study were members of the Benteng Panynyua English Club (BPEC) Makassar. For data collection, researchers used the Observation Checklist as an instrument for collecting data from the sample.The research results from the observation checklist suggest that there are 8 qualities that need to be considered in determining whether there is Emphatic Listening in BPEC and how to apply it. First, attendance. 57% of members from meetings 1,2&3 attended and participated in the discussion. Second, compassion, 75% of members apply this quality. Third, wisdom. 75% applied this quality. Fourth, not judgmental. 70% of members do not justify other people's opinions. Fifth, trustworthiness. 25% occurred during the discussion because this quality depends on the topics discussed during the discussion. Sixth, 100% patient was applied. Seventh, responsive. 100% of members responded well. Eighth, focus your attention. 100% of members implement this, such as not using electronic devices when discussing except when necessary.Based on the findings of this researcher it was found that there was emphatic listening and it was applied well to all members of the BPEC discussion.